A report on the practice in industry training in fish capture. - Oberes, Jesus D. (College of Fisheries, University of the Philippines, 1957)
After two years to theory and practice in the institute, the students are requested to go out for apprenticeship in order to practice further the groundwork to gain better knowledge or know-how in the fishing industry. It is a common tradition of the institute that every students in his or her particular selected course to practice at least six months. In the field, during my apprenticeship I aboard fishing vessels of different tonnage, I was inclined to work from morning to sunset as an ordinary fisherman. Although commercial fishing has been know to exist since the time when men begins to catch fish more than what he can use, the Philippine has been in many years and even to the present importing canned goods for her increasing population. Our economy is always based on rice and fish for our existence. Based on this basis, we have to produce more fish to replenish the ever-increasing demand of fishery products, not only in our country but also our neighbours in Southeast Asia. With the importance for fish protein in our economy, it is becoming necessary to protect further our grounds from depletion by some unsculprous fishermen. Who are considered criminal because they used dynamite and other illegal methods to kill or destroy our fish population. This completion of my monthly progress report as practiced in the fishing industry in the Philippines has been limited only to all legal fishing in the Philippines. If our government could only afford to support those poor fishermen and introduces those modern method of fishing which were introduced and found effective in our fishing. I see no reason why we cannot produce enough fishery products that will ultimately solve one of our big problems in our country, that of saving our dollar resources.